Pedoman Kepatuhan dalam Pengelolaan Pasien dengan stabil Angina/Non-STEMI tanpa PCI Prosedur (Registry Medis Dikelola) - Erwinanto Erwinanto; Angke Widya; Nahar Taufik; Sri Diniharini; Dolly Kaunang; Arini Setiawati (Jurnal Kardiologi Indonesia, 2014)
Aim: To document current usage of antiplatelet therapy and the implementation of ACC/AHA 2007 guideline in the clinical management of unstable angina/ non-ST-elevation myocardial infarction (UA/NSTEMI) patients not undergoing PCI procedure in Indonesia (medically managed) and their risks according to Global Registry of Acute Coronary Events (GRACE) score as well as in-hospital mortality.Method: A multicenter observational, prospective disease registry, recruiting patients with UA/NSTEMI. No specific treatment will be recommended in this disease registry. Data will be collected based on Physician’s applicable daily practices without any intervention.Results: A total of 467 eligible patients, 246 patients with UA and 221 with NSTEMI, aged 18 years or older were recruited from 18 hospitals during December 2009 – January 2011. Most recruited patients were at low risk (63.9%) and only 0.9% patients were at high risk according to the GRACE score. Patients were treated with ASA (90.6%) and Clopidogrel (96.6%) when they reached the emergency department. Medical therapy instituted during hospitalization were injectable anticoagulant (91.4%), oral anticoagulant (0.9%), oral nitrate (82.7%), beta blocker (60.8%), ACE inhibitor (49%), angiotensin receptor blocker (20.3%), calcium channel blocker (19.9%), statin (13.1%), and other medications given according the presentation of complications or comorbidities. In-hospital mortality was documented in 3.2% of patients. At discharge ASA was given to 87.6% and clopidogrel to 94.2% patients.Conclusion: The result showed that most of the patients admitted with UA/NSTEMI were at low or moderate risk according to GRACE score. Although treatment with antiplatelet and anticoagulant largely followed the ACC/AHA guidelines, however, this registry documented under treatment of other medications such as ACE-inhibitors and beta blockers. Reinforcement of the guideline compliance and continuous medical education would provide better outcomes for the patients.